Penentuan Isoterm Adsorpsi Komposit Spent Bleaching Earth (SBE) - Mushroom Substrate (SMS) Sebagai Adsorben Logam Cu2+ - Rezeki, Muhammad Dio; Yenie, Elvi; Darmayanti, Lita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Copper (Cu) is a heavy metal that is toxic and can accumulated in the body. The limits of the highest concentration of this element in contamined waters range from 1-5 mg/l. Adsorption is a simple method that has proven to be quite enough effective to treating liquid waste. Isotherms of adsorption shows that the variations of adsorben and adsorbate that occur in solution at constant temperatures. The adsorption approach model in this study is isothermic adsorption. The determination of Cu2+ metal adsorption isotherms by the SBE-SMS adsorben composite is determined using the linear regression method and from the regression equation will be obtained the R2 value. The relation coefficient value from the Langmuir isother equation is obtained the value of R2 = 0.4065 and in the Freundlich isother equation obtained the value of R2 = 0.6999. From the results of Cu2+ metal adsorption research using adsorben composite spent bleachin earth (SBE) – spent mushroom substrate (SMS) it is known that isotherms adsorption that occurs following isotherm Freudlich model.Key words: Composite, Copper (Cu), Isotherm Adsorption, Spent Bleaching Earth (SBE), Spent Mushroom Substrate (SMS)